INTEGRATING QUR'ANIC PEDAGOGY WITH CONTEMPORARY EDUCATIONAL FRAMEWORKS: A THEMATIC EXEGESIS APPROACH TO HOLISTIC STUDENT DEVELOPMENT - Muflikhatun, Muflikhatun; Akmansyah, Muhammad; Amirudin, Amirudin; Fatoni, A.; Nisa, Auwliya Khairun; Bhatti, Muhammad Safdar (Program Studi Pendidikan Agama Islam Tarbiyah IAI Muhammadiyah Bima, 2026)
This study explores the integration of Qur'anic teaching methods into modern educational frameworks, focusing on holistic student development. The research addresses the limitations of traditional educational practices that primarily emphasize intellectual skills, overlooking emotional, spiritual, and participatory growth. By applying thematic exegesis (tafsir mawdhu’i), this study synthesizes key Qur'anic principles hikmah (wisdom), mau’izhah hasanah (compassionate advice), and shura (consultation) and aligns them with contemporary pedagogical theories. The study utilizes a qualitative approach, employing literature review and thematic analysis to examine the application of these principles in fostering critical thinking, emotional intelligence, and collaborative learning. Findings reveal that integrating Qur'anic pedagogy into modern education enhances cognitive, emotional, and social development, contributing to the creation of more balanced and ethical learning environments. The study concludes that the incorporation of these Qur'anic methods provides a comprehensive framework for educators to cultivate well-rounded students capable of navigating modern educational and societal challenges. Recommendations include further research on the systematic application of these principles across diverse educational contexts.